The relationship Between The Smoking Habits Of Family Members And The Incidence Of Respiratory Infections Of Children Under 5 Years In Indonesia: A Literature Review - Puspita Sari, Mita Yuniar; Khoiriyyah, Khoiriyyah; Setyowati, Dewi (Jurnal MIDPRO, 2023)
Â Background : Reducing under five mortality is one of the SDGS aims for ensuring a healthy life and supporting wellbeing for all ages. When it comes to causes of death in babies and young children, acute respiratory infections always come in first. Cigarette smoke is one of the air pollutants that increases the occurrence of respiratory system disorders. The goal is to examine the connection between family members' smoking behaviors and the prevalence of ARI in young children. Methods: This literature review is sourced from various research articles, and official websites published in 2018-2022. Search articles using keywords, inclusion and exclusion criteria. Article assessment use CASP and article processing uses the Mendeley application Results: Determined 6 sources of articles that are feasible and relevant to be used after passing the critical appraisal stage. Conclusion: There is a connection between family members' smoking behaviors and the prevalence of acute respiratory infections..